Tropical liver disease. (November 2019) - Beeching, Nick; Dassanayake, Anuradha
Abstract: The liver is frequently involved in infections that are prevalent in different regions of the tropics, and chronic liver disease, sometimes with multiple aetiological explanations, is an important cause of early morbidity and mortality. This article describes some hepatic and biliary problems that are seen in the tropics or can be imported from resource-poor settings. The epidemiology of hepatitis A is changing in some areas, and hepatitis E is now recognized in an increasing range of tropical and non-tropical settings. Vaccines have been developed against hepatitis E. Hepatitis B and C continue to cause chronic liver disease, cirrhosis and hepatocellular carcinoma, but these can be eclipsed in epidemiological importance by the sequelae of the emerging epidemic of non-alcoholic fatty liver disease in many parts of the tropics. The pathophysiology of acute and chronic liver disease caused by aflatoxins is better understood, as is the relationship of veno-occlusive disease of the liver to pyrrolizidine alkaloids. Self-poisoning with hepatotoxins is common in many countries. The diagnosis and management of cystic hydatid disease of the liver has been rationalized, based on a systematic approach to the classification of imaging findings.